Nostalgia as a Diasporic Representation in Govinda Raj Bhattarai’s Muglan - Rai, Ram Prasad (Humanities and Social Sciences Journal, 2021)
The major focus of this paper is on ‘nostalgia’ as a diasporic representation in Muglan, a novel by Govinda Raj Bhattarai. The main characters Sutar Kanchho, Thule, Shekhar Karki, Rai Kanchho and many others leave home in the eastern Nepal and go to India for joining the Indian army. When they are misguided to Bhutan from Siliguri, India and made to work in the Road Construction site, they know that their dream of being army and earn a lot for their families can never come true. They are forced to work hard for almost no payment. Some of them die of hunger. They remember home, family members, cattle, field and relatives in their village in Nepal. They hope to return home one day, but that day never comes. Some of them die helplessly. Because of extreme exploitation over them, they feel alienated and displaced which cause nostalgia in them. Since nostalgia is one of the important features of diaspora, the experience of the characters in Muglan is diasporic. As this study is based on qualitative research the researcher has consulted books, reviews and journal articles related to ‘nostalgia’ and ‘diaspora.’ This is a new concept in the research on Muglan. It will be a new way for the support of the upcoming researchers in the concerned area.